Research on Application of PPPoE+ Technology in Broadband Access Network - Zhe Du; Jun Zhu; Chengbin Shen; Ming Jiang (Dianxin kexue)
Along with large-scale FTTx access network construction and massive users upgrade from DSL to FTTx, bundling between user account and access equipment physical port is an important function to achieve accurate user identification for telecom operators. The principle and implementation of PPPoE +-based broadband user identification technology were introduced. Implementation status of broadband access network equipments' PPPoE+function was investigated. Application strategy of PPPoE+ in the broadband access network was discussed.